A Unique Volcanic Jatibarang Reservoir: Facies Characterization and Fracture Calculation - Benyamin*, Benyamin; Pratiwi, Pratiwi; Indah, Fitriani (Aceh International Journal of Science and Technology, 2022)
Jatibarang structure, situated in Jatibarang low, one of the prolific sub-basin in the northwest Java basin, belongs to PT. Pertamina EP working area. One hundred seventy wells have been drilled, from which there were 56 production wells. Forty production wells were sunk on a volcanic reservoir. Since 1970, volcanic Jatibarang has faced disputed facies concepts, porosities heterogeneity, and permeability system. A fractured reservoir model was proposed. It was due to unique high-performance hydrocarbon in the early years, steeply depleted in the next 3 years, and flat over 20 years. A unique petrophysical method was developed with various explosives and effusive facies. This study proposes a new facies determination concept related to unavailable default petrophysical plots usually used in the clastic-carbonate reservoir. The new concept of formation evaluation attempts to distinguish the fractured vitric tuff reservoir and non-reservoir zone, which is both effusive lava and explosive product. Reservoirs differed from common clastic-carbonate, typically high gamma-ray reservoirs due to potassium feldspar composition. The fracture existence is reflected by a sonic overrunning density log aligned with a deep resistivity pattern. The width of the fracture apertures was measured, and spacing intensities were calculated. Finally, fracture permeability was estimated comprehensively to describe reservoir performance. Property models built with only sonic and triple combo have been debatable; however, advanced logging of JTB-211 has proven this accuracy method.